Acceleration analysis of repetitive multi-MeV ion beams from pulsed plasmas - M.V., Roshan; Nadia Vahdat, Roshan; Arwinder, Singh (Elsevier Ltd., 2023)
Multi - MeV ion spectra reproduced with absolute spectral index agrees with the experimental data and meet the needs to critically analyze the repetitive pulsed plasma mode of applications. The ion acceleration parameter, , predicts mean ion energy and that is related to the electric discharge components based upon the precision measurements. Proper selection of repetition rate offers a relatively stable proton beam to acquire the survival curves of irradiated targets. DSB rate for plasma focus operated at , is with corresponding surviving probability of the order of . The surviving fraction is likely to be more affected by higher dose frequencies.